Analisis Kinerja Perusahaan dan Pajak Penghasilan Sebelum dan Setelah Berlakunya UU PPH Tahun 2008 - Irawan, Ronny (Jurnal Akuntansi Kontemporer, 2011)
This research is to examine whether the tax reform in 2009h os an impact on the firm's performance. The main points of reformation are a change of tax income tarif dan the tax facilities for public company. Examinations of performance were performed two years and one y ear before tax reform compared to performance o f two and one years after tax reform. Using Wilcoxon Signed Rank Test, testing for manufacturing companies registered in Indonesian Stock Exchange, this research proving that there was no significant differences of corporate t ax ratio between before tax reform with after tax reform. Meanwhile, generally the performance (profitability, liquidity, leverage of manufacturing companies before tax reform a re significant different with performance o f manufacturing companies after tax reform.